A two-year report of a comparative randomized controlled trial on the treatment of upper central incisors with periapical lesions - Daniele Angerame; Matteo De Biasi; Vittorio Franco; Lorenzo Bevilacqua; Attilio Castaldo (Giornale Italiano di Endodonzia, 2017)
Aim: To evaluate the two-year success rate of primary root canal treatment performed with two integrated shaping and filling systems on upper central incisors with chronic periapical pathosis. Methodology: The trial enrolled 60 patients with an untreated maxillary central incisor presenting a chronic periapical lesion smaller than 5 mm in diameter, who were randomly assigned to two treatment groups: G1 (n = 30), Revo-S/One Step Obturator; G2 (n = 30) GTX/GTX Obturator. The patients underwent single-session root canal treatments by an experienced endodontist and were followed up for two years. The clinical evaluation entailed percussion and palpation tests. Two independent examiners rated the radiographic healing on the basis of a previously described scale. Comparability between groups in terms of baseline clinical parameters was tested with a Mann-Whitney test (age, apical gauging) and χ2 test (tenderness to percussion and palpation). The comparison of clinical data and radiographic healing scores between the groups and among time points was carried out with non-parametric statistical methods (p < 0.05). Results: The two groups were comparable in terms of baseline clinical parameters. All patients were available for the re-evaluation after two years. Only one patient per group was positive to the clinical tests at the final recall. An improvement of radiographic healing scores along the follow-up period was observed. After two years, the lesions were scored as totally healed, partially healed and not healed in 93.3%, 3.3% and 3.3% of cases in G1 and in 93.3%, 0% and 6.7% of cases in G2, without pointing out statistically significant differences between groups. Conclusions: Both the two tested integrated shaping and filling systems proved to be effective for the treatment of upper central incisors with periapical pathosis. When monitoring the healing of periapical lesions, follow-up times longer than one year may be required to observe complete healing.